Benefits of the enhanced recovery after surgery pathway for orthognathic surgery. Issue 2 (February 2022) - Stratton, M.; Waite, P.D.; Powell, K.K.; Scopel, M.M.; Kukreja, P.
Abstract: The enhanced recovery after surgery (ERAS) protocol was designed to improve patient outcomes and decrease complications, opioid use, and postoperative nausea and vomiting (PONV). The aim of this retrospective cohort study was to examine the effectiveness of ERAS protocols implemented in orthognathic surgeries from 2017 to 2018 at the University of Alabama at Birmingham Hospital by measuring opioid use and PONV. Two groups were identified through chart review, a non-ERAS group (traditional) of patients who had surgery without a protocol and an ERAS group of patients who had surgery with the ERAS protocol. The anesthesia and surgical teams followed a standardized protocol for perioperative management. All procedures were performed by a single surgeon and included single- and double-jaw surgeries and adjunctive procedures. The patient charts were analyzed for postoperative opioid consumption (measured in morphine milligram equivalents, MME) and PONV. IBM SPSS Statistics version 26 was used to conduct the statistical analyses. The ERAS group received less opioids during the postoperative period than the control group (31.2 MME vs 54.6 MME, P = 0.002). The ERAS group also had a lower incidence of PONV, with 1.2 episodes of PONV compared to 2.4 episodes in the non-ERAS group ( P = 0.008). This study demonstrates that the ERAS protocol is effective in decreasing postoperative opioid consumption and PONV.